Strategic corporate responsibility and green management : perspectives and issues in emerging economies - Das Gupta, Ananda (Emerald Publishing Limited, 2023)
Corporate social responsibility has increased exponentially throughout the past decades and is of growing importance to the success of businesses internationally. Green management especially is at the forefront of new developments and initiatives in the face of the climate crisis, aiming to mitigate fundamental institutional misalignments in controlling drastic expansion and its adverse consequences on the environment. Strategic Corporate Responsibility and Green Management turns the focus to emerging economies, in particular India and Mexico. Offering both criticism and examples of effective projects, the chapter authors consider the technological solutions for womens empowerment in India, waste management for combating COVID-19, a case study of Coca Cola in India and the tragedy of the commons, corporate responsibility in MSMEs, a study of Mexican companies and corporate social responsibilities impact on the sustainable development goals, and errors in corporate social responsibility. This volume of Critical Studies on Corporate Responsibility, Governance and Sustainability harnesses corporate responsibility and green management to integrate social and environmental concerns into productive business operations, paving the way for future successes in emerging economies. The series facilitates idea exchanges and research collaborations between developed and developing countries, and between the West and the East. It promotes best ideas, values, practices and innovations in corporate governance, corporate responsibility and sustainability in the world and encourages holistic thinking, cross-disciplinary research, multiple perspectives and the use of various research approaches and methods.
Keywords: Social responsibility of business -- Developing countries.; Sustainable development.; Business & Economics -- Development -- Sustainable Development.; Business ethics & social responsibility.; elektronické knihy; electronic books